Current state and prediction of the future of digitization as a part of Industry 4.0 - Zauskova, Anna; Kusa, Alena; Kubovics, Michal; Scepkova, Simona; Urminova, Marianna (Serbian Journal of Management, 2022)
The world has changed as a result of the expansion of Industry 4.0. Big data, machine learning or automation and robotics dominate almost all business entities. As a result of the digital revolution, we are seeing a boom in the application of various digital techniques. To achieve profitability, eliminate losses and start-up costs, as well as to improve competitiveness, businesses implement digitization in various company processes. The aim of this paper is to map and clarify the interaction between Industry 4.0 and digitization. The result is a content analysis, with which we will point out the importance of applying the principles of digitization at a practical level. The paper reflects an examination of the current state of the digital boom and its impact on small and medium-sized companies. The main benefit of this paper is to examine and point out the current level of digitization of the surveyed business entities through our own questionnaire survey. We selected the area of digitization from the collected results, specifically five research questions were determined for the analysis, which we identified before the questionnaire survey. A questionnaire survey was also conducted in Bulgaria, Serbia and the V4 partner countries.
Keywords: digitization; present phenomenon; small and medium enterprises; online marketing communication; industry 4.0